Changes in diffusion parameters, energy-related metabolites and glutamate in the rat cortex after transient hypoxia/ischemia - Homola, Aleš; Zoremba, Norbert; Šlais, Karel; Kuhlen, Ralf; Syková, Eva (Neuroscience letters, 2006)
It has been shown that global anoxia leads to dramatic changes in the diffusion properties of the extracellular space (ECS). In this study, we investigated how changes in ECS volume and geometry in the rat somatosensory cortex during and after transient hypoxia/ischemia correlate with extracellular concentrations of energy-related metabolites and glutamate. Adult male Wistar rats (n = 12) were anesthetized and subjected to hypoxia/ischemia for 30 min (ventilation with 10% oxygen and unilateral carotid artery occlusion). The ECS diffusion parameters, volume fraction and tortuosity, were determined from concentration-time profiles of tetramethylammonium applied by iontophoresis. Concentrations of lactate, glucose, pyruvate and glutamate in the extracellular fluid (ECF) were monitored by microdialysis (n = 9). During hypoxia/ischemia, the ECS volume fraction decreased from initial values of 0.19 +/- 0.03 (mean +/- S.E.M.) to 0.07 +/- 0.01 and tortuosity increased from 1.57 +/- 0.01 to 1.88 +/- 0.03. During reperfusion the volume fraction returned to control values within 20 min and then increased to 0.23 +/- 0.01, while tortuosity only returned to original values (1.53 +/- 0.06). The concentrations of lactate and glutamate, and the lactate/pyruvate ratio, substantially increased during hypoxia/ischemia, followed by continuous recovery during reperfusion. The glucose concentration decreased rapidly during hypoxia/ischemia with a subsequent return to control values within 20 min of reperfusion. We conclude that transient hypoxia/ischemia causes similar changes in ECS diffusion parameters as does global anoxia and that the time course of the reduction in ECS volume fraction correlates with the increase of extracellular concentration of glutamate. The decrease in the ECS volume fraction can therefore contribute to an increased accumulation of toxic metabolites, which may aggravate functional deficits and lead to damage of the central nervous system (CNS).
Keywords: Animals; extracelulární prostor; Rats; Kinetics; Rats, Wistar; Hypoxia-Ischemia, Brain; Extracellular Space; Lactic Acid; kyselina mléčná; energetický metabolismus; kyselina pyrohroznová; Energy Metabolism; mozková hypoxie a ischemie; Microdialysis; mikrodialýza; Pyruvic Acid; kyselina glutamová; Male; modely nemocí na zvířatech; glukosa; Glucose; Disease Models, Animal; krysa rodu Rattus; mozková kůra; Cerebral Cortex; zvířata; mužské pohlaví; kinetika; Glutamic Acid; potkani Wistar